Child Abuse and Epigenetic Mechanisms of Disease Risk - Yang, Bao-Zhu (2013)
BACKGROUND: Child abuse is highly prevalent and associated with increased risk for a range of health problems including: cancer, cardiovascular disease, diabetes, psychiatric disorders, and other health problems. Little is currently known about the mechanism by which early adversity confers risk for health problems later in life. PURPOSE: To determine if there are epigenetic differences associated with child maltreatment that may help explain association between adverse childhood experiences and later health problems. METHODS: As part of a study examining genetic and environmental factors associated with depression, saliva DNA specimens were collected on 96 maltreated children removed from their parents due to abuse or neglect and 96 demographically-matched control children between 2003 and 2010. In 2011, the Illumina 450K BeadChip was used on stored DNA specimens and analyzed to examine whole-genome methylation differences between maltreated and control children. RESULTS: After controlling for multiple comparisons, maltreated and control children had significantly different methylation values at 2868 CpG sites (p< 5.0 × 10(−7), all sites; average methylation difference per site=17%; range 1%–62%). The gene set contained numerous markers of diseases and biological processes related to the health problems associated with early childhood adversity. CONCLUSIONS: While replication is required, this study suggests that epigenetic mechanisms may be associated with risk for health problems later in life in maltreated children. This study lays the groundwork for future studies examining health and methylation measures to further characterize the role of epigenetic mechanisms in conferring risk for medical problems in individuals with histories of early adversity.